2017
DOI: 10.14740/gr732w
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Mesenteritis: Multidisciplinary Collaboration Is Essential for Diagnosis and Treatment

Abstract: Sclerosing mesenteritis (SM) is an extremely rare disease characterized by chronic non-specific inflammation, fat necrosis and fibrosis of the mesentery. We presented a 77-year-old man with progressive dyschezia, abdominal pain and mass in left lower quadrant. Computed tomography (CT) exhibited a thickened mesentery, enlarged lymph nodes and strand-like densities around the mesenteric vessels. However, laboratory investigation, colonoscopy and positron emission tomography did not provide any specific results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…5 Sclerosing Mesenteritis is characterized by fat degeneration, necrosis, chronic inflammation, scarring and eventually fibrosis of the fatty tissue within the mesentery. 7 The most commonly affected are the mesentery of the small bowel and the mesoappendix even though the large bowel mesentery is less commonly affected. 8 The exact mechanism is unknown; however, several conditions have been associated with SM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Sclerosing Mesenteritis is characterized by fat degeneration, necrosis, chronic inflammation, scarring and eventually fibrosis of the fatty tissue within the mesentery. 7 The most commonly affected are the mesentery of the small bowel and the mesoappendix even though the large bowel mesentery is less commonly affected. 8 The exact mechanism is unknown; however, several conditions have been associated with SM.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms included weight loss, diarrhea, vomiting, anorexia, constipation, bloating, malaise, nausea, pain with eating and fatigue. 6 He H et al, 7 reported a 77years old male who presented with dyschezia, abdominal pain and mass in left lower quadrant and Katsuya Endo et all reported a 22years old Japanese male who presented with chronic abdominal pain and small intestine mesentery mass. 7,21 Harvin G reported a case of SM who presented with intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sclerosing mesenteritis is non-specific inflammatory mass-forming lesion in the mesenteric connective tissue that is characterized by variable degrees of fibrosis, chronic inflammation, and fat necrosis [ 1 5 ] and mainly affects the mesentery of the small bowel [ 2 9 ]. Although the exact etiology of sclerosing mesenteritis has not been elucidated [ 1 6 , 9 14 ], it has been reported that the possible risk factors for the disease include malignancy, autoimmune disease, infection, ischemia, trauma, and a history of previous surgery [ 3 , 5 , 8 , 11 , 12 ]. Sclerosing mesenteritis is sometimes indistinguishable from neoplasms because its manifestations and radiographic findings may be identical to those of malignancies [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%